Low-intensity low-temperature analysis of perovskite solar cells for deep space applications. (9th December 2022) - Colenbrander, Tyler; Peng, Jun; Wu, Yiliang; Kelzenberg, Michael; Huang, Jing-Shun; MacFarland, Clara; Thorbourn, Dennis; Kowalczyk, Robert; Kim, Wousik; Brophy, John; Bui, Anh Dinh; Nguyen, Dang-Thuan; et al.
Abstract : Perovskite solar cells (PSCs) are studied in low-intensity low-temperature (LILT) conditions before and after low energy proton irradiation to characterize device performance at deep space mission-relevant light intensities and temperatures. Abstract : High specific power (power per mass) ultralight solar arrays made of perovskite solar cells (PSCs) are being considered to power spacecraft in deep space conditions as far as Neptune (30 AU). To understand how PSCs perform and respond in deep space, we characterize PSCs under low-intensity low-temperature (LILT) conditions before and after low-energy proton irradiation. PSCs show promising performance characteristics under most LILT conditions even after exposure to low-energy protons. However, the measured cell efficiency tends to decrease at extreme lower temperatures, suggesting that further research into cell architectures and materials could improve PSCs for deep space applications.